Bermuda : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2008)
In the case of Bermuda, application of risk-based approaches seems particularly relevant not only to the insurance sector, but also to other types of financial and nonfinancial activities. The legal framework for investigation and prosecution of money laundering (ML) is well developed, and law enforcement and prosecutorial staff are highly motivated and professional. Bermuda's Financial Investigation Unit (FIU) should be more adequately funded, staffed, and provided with additional technical resources, including, for instance, expertise in forensic accounting. A key strength of Bermuda's supervisory regime is the integrated nature of financial sector supervision.